Potable Drinking Water in Nigeria’s Coastal Communities: Insights from Physico-chemical and Bacteriological Properties Assessment of Kurutie’s Water and Distribution Systems - Joyce E Idomeh; Kabari Sam; Abraham Ogheneruemu Ekperusi; Nnenna A Isokpehi (Ethiopian Journal of Environmental Studies and Management, 2024)
Access to clean and safe water is not only crucial for maintaining good health but also plays a pivotal role in driving socio-economic progress for the popula on. In this study, we sampled portable water sources from Kurutie’s community to assess the physical, chemical, and bacteriological attributes of the water whether it meets the water quality criteria for human consumption using standard laboratory procedure. The results of physicochemical parameters like pH (6.60±0.08), conductivity (241.01±4.36 µs/cm), total dissolved solids (127.36±0.27 mg/l), dissolved oxygen (4.68±0.45 mg/l), temperature (27.04±0.06 °C), chlorine (0.21±0.2 mg/l), salinity (49.67±0.34 mg/l) and total petroleum hydrocarbons (0.04±0.05 mg/l) were within national and international limits, while turbidity (9.12±0.35 NTU), total (22 CFU/100 ml) and faecal coliforms (1 CFU/100 ml) were found to have exceeded the recommended limits of 5 NTU, and 0 CFU/ML respectively in Kurutie’s groundwater and distribution systems. The total coliform counts indicated bacterial contamination. Isolates reported include Shigella, Escherichia, Salmonella, Enterobacter, Pseudomonas, Proteus, Staphylococcus, and Bacillus. Poor waste management practices like open defecation and indiscriminate waste disposal could result in the elevated turbidity and coliform counts observed. In light of this result, water from the only borehole serving the community could be deemed unfit for human consumption as it relates to health risks and safety. It is imperative that regular surveillance of the groundwater and the distribution channel is necessary to ensure clean and safe water for the human population in Niger Delta communities.
Keywords: Drinking water monitoring; microbial assessment; TPH; water quality; portable drinking water; physicochemical parameters